1990
DOI: 10.1111/j.1467-6494.1990.tb00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, Traits, and the Stages of Human Courtship: Qualifying the Parental Investment Model

Abstract: Individual differences are explicitly connected to social interaction in Darwin's notion of sexual selection. Traits that increase the probability of successful reproduction will tend to increase in frequency. This process operates partly through differential choice, by one sex, of certain traits in the other. According to the parental investment model, females frequently have more stringent criteria for the traits they will accept in a mate because they have a relatively larger investment in each offspring. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
404
1
17

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 619 publications
(456 citation statements)
references
References 18 publications
34
404
1
17
Order By: Relevance
“…r Alternatively, the one-sided gender bias hypothesis states that men, more than women, selectively attend to attractive members of the other sex. This hypothesis is consistent with research suggesting that men value physical attractiveness in potential mates relatively more than females do (Buss, 1989;Feingold, 1990Feingold, , 1992Kenrick et al, 1990). For example, women shown photos of physically attractive men did not alter their commitment to their partners, as men did when exposed to physically attractive women .…”
Section: Physical Attractiveness and The Eye Of The Beholdersupporting
confidence: 81%
See 2 more Smart Citations
“…r Alternatively, the one-sided gender bias hypothesis states that men, more than women, selectively attend to attractive members of the other sex. This hypothesis is consistent with research suggesting that men value physical attractiveness in potential mates relatively more than females do (Buss, 1989;Feingold, 1990Feingold, , 1992Kenrick et al, 1990). For example, women shown photos of physically attractive men did not alter their commitment to their partners, as men did when exposed to physically attractive women .…”
Section: Physical Attractiveness and The Eye Of The Beholdersupporting
confidence: 81%
“…This hypothesis is consistent with theory and evidence that men tend to value highly the physical attractiveness of potential romantic partners (e.g., Buss & Schmitt, 1993;Kenrick, Sadalla, Groth, & Trost, 1990) and that women value the physical attractiveness of shortterm (Buss & Schmitt, 1993;Gangestad & Simpson, 2000) and extra-pair partners (Scheib, 2001). r Alternatively, the one-sided gender bias hypothesis states that men, more than women, selectively attend to attractive members of the other sex.…”
Section: Physical Attractiveness and The Eye Of The Beholdersupporting
confidence: 76%
See 1 more Smart Citation
“…Consistent with this view, both men and women are better at assessing strength in men than in women (17). In contrast, in mammals such as humans, access to female sexuality was a far greater limiting factor for male fitness than access to male sexuality was for females (29)(30)(31). Insofar as attractiveness reflects fertility and offspring fitness, even small changes in the probability of a woman's granting sexual access constitute a powerful benefit.…”
Section: Engineering Analysismentioning
confidence: 60%
“…Researchers have found that heterosexual women look for a partner with high socio-economic status and heterosexual men look for a partner who is physically attractive (Buss & Barnes, 1986;Kenrick, Sadalla, Groth & Trost, 1990;Ellis & Symons, 1990;Townsend, 1993). The fake female profiles typically contained physically attractive women and women in need of support.…”
Section: Theoretical Explanationmentioning
confidence: 99%